The Impact of Implementing the Independent Curriculum Based on Project-Based Learning on Arabic Reading Skills (Maharoh Qirāah) at State Islamic Junior High School - Hairuddin Arsyad; Asep Sopian; Maman Abdurrahman; Bening Anjaswara (Jurnal Iqra' : Kajian Ilmu Pendidikan, 2025)
This study aims to analyze the impact of implementing the Independent Curriculum based on Project-Based Learning (PjBL) on Arabic reading skills (Maharoh Qirāah) in learning at Madrasah Tsanawiyah Negeri 1 Bandung. This study employs a qualitative approach, collecting data through observations, interviews with Arabic language teachers, student questionnaires, and documentation of learning activities. The results indicate that the implementation of the Independent Curriculum based on PjBL has a positive impact on Maharoh Qirāah learning. The project-based approach has been proven to enhance students' interest and motivation, placing them in the "very good" category. Additionally, the quality of the learning process has significantly improved, accompanied by an increase in students' learning outcomes and competencies, both of which are rated as "very good". These findings were obtained through an analysis of observation data, interviews, and questionnaire results. The interview data with Arabic language teachers was reinforced by questionnaire responses containing 15 statements covering three main components. The implementation of the Independent Curriculum has also facilitated teachers in designing more engaging and interactive learning materials. Ultimately, this study confirms that the integration of Project-Based Learning within the Independent Curriculum framework is not merely a pedagogical alternative but a strategic approach that substantially strengthens the effectiveness of Arabic reading instruction. By simultaneously enhancing student motivation, learning quality, and academic achievement, this model contributes meaningfully to the development of more adaptive, student-centered, and outcome-oriented Arabic language education. These findings therefore offer both theoretical enrichment and practical direction for educators and curriculum developers seeking to elevate the standard of Maharoh Qirāah learning in Islamic secondary education.